2022
DOI: 10.20377/jfr-701
|View full text |Cite
|
Sign up to set email alerts
|

Childcare and housework during the first lockdown in Austria: Traditional division or new roles?

Abstract: Objective: This study analyses how much time mothers and fathers spent on childcare and housework during and after the first COVID-19 lockdown in Austria (starting in mid-March 2020) and how they distributed that time between themselves. Background: Parents needed to reallocate care work between themselves as, on the one hand, kindergartens and schools closed for two months and, on the other hand, employment-related changes arose, e.g., working from home. The results are discussed in light of major theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…This recent research showed ambiguous results (for an overview, see Jessen et al, 2022). For Germany, some studies found that men spent more time on caregiving that is related to changes in work arrangements and rising possibilities of teleworking (Berghammer, 2022; Jessen et al, 2022, for Austria), but most studies agree that mothers still took on the central role in childcare during the pandemic. Others detected that unpaid care intensity among (unemployed) women and the corresponding gender inequalities had increased (Camiletti & Nesbitt‐Ahmed, 2022; Corsi & Ilkkaracan, 2022; Hank & Steinbach, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This recent research showed ambiguous results (for an overview, see Jessen et al, 2022). For Germany, some studies found that men spent more time on caregiving that is related to changes in work arrangements and rising possibilities of teleworking (Berghammer, 2022; Jessen et al, 2022, for Austria), but most studies agree that mothers still took on the central role in childcare during the pandemic. Others detected that unpaid care intensity among (unemployed) women and the corresponding gender inequalities had increased (Camiletti & Nesbitt‐Ahmed, 2022; Corsi & Ilkkaracan, 2022; Hank & Steinbach, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A general consensus across many countries is that additional childcare responsibilities fell disproportionately on mothers, who increased their already higher amounts of childcare, but that fathers also increased time spent on childcare compared to before the pandemic (Craig & Churchill, 2021;Hank & Steinbach, 2021;Kreyenfeld & Zinn, 2021;Mangiavacchi et al, 2021;Margaria, 2021;Shafer et al, 2020). Some researchers have found that fathers took on new roles as parents tried to figure out ways of working and home schooling (Berghammer, 2021;Petts et al, 2021). The next question will be to consider the longer-term consolidation of these new roles.…”
Section: Covid 19 Policy Response and Fathersmentioning
confidence: 99%
“…Collins et al, 2021;Hipp & Brünning, 2021;Yerkes et al, 2020). Many studies have concluded that despite changes to childcare time, the pandemic has rather reinforced the gendered division of work and sent us backwards in this regard (Berghammer, 2021;Blum & Dobrotić, 2022, Cheng et al, 2021Farré et al, 2020).…”
Section: Covid 19 Policy Response and Fathersmentioning
confidence: 99%
“…The sharing of professional and care work, which is always gendered, inevitably had to be renegotiated after the outbreak of the Covid-19 pandemic in the spring of 2020, especially during the imposed containment measures. Numerous studies and research findings indicate a "re-traditionalization" (Allmendinger, 2020) regarding gender roles and a gender-specific division of labor as care work is borne primarily by women (e.g., Berghammer, 2022;Craig, 2020). Professionals who were expected to remain in their home office during the pandemic were particularly challenged because they also had to manage childcare, homeschooling, and housework in the time they normally had exclusively for professional obligations.…”
Section: Introductionmentioning
confidence: 99%